From “Lapp” to “Margrete". Representation of Sámi People in Photographic Postcards from Norwegian Sápmi - Schøning, Eli-Anita Øivand (UiT Norges arktiske universitet, 2018)
This master’s thesis examines how Sámi people were represented in postcards from Norwegian Sápmi during the late 19th century to present day. The study explores how postcards can unveil both grand narratives and personal and local stories. Portraying Sámi people and culture as exotic and different, is a commonality in touristic representations of the Sámi. Postcards with Sámi motifs are no exception. I argue that the postcards depict the Sámi in an “emblematic” way, through a focus on nature, reindeer herding and traditional clothing. This kind of representation is not only conducted by outsiders, and I maintain that emblems are likely to be utilized as a strategy to satisfy the demands in the tourism market. Postcards trigger memories, and can therefore be used to bring personal and local stories to the forefront. As such they serve to individualize rather than objectify, reconstruct stories of the past, and shed light on Sámi agency. Further, postcards can be instruments for the Sámi themselves. When they produce their own postcards, or repatriate old postcards through artistic work, the postcards become powerful tools in revitalization processes and contribute in shaping Sámi identities.